L'emploi hypothétique de AND dans Everyman et en moyen-anglais - Fabienne Toupin (Anglophonia)
This paper deals with the conjunction and in the English late medieval period when it displayed not only the senses that we are familiar with in Present-Day English, but also a whole range of conditional meanings for which if would be used today. My initial corpus is the fifteenth-century morality play called Eveiyman, butfurther enquiry will show that the conditional meaning was in fact a regular and attested use of and throughout Middle English. After demonstrating that it is impossible for this use of and to have originated in loan translation from Dutch or in contact with Scandinavian, I will try to build a case for a grammaticalisation process. The driving force behind the process would have been a metonymical semantic shift from the temporal senses of the conjunction in the late twelfth or in the early thirteenth century. I will also sketch the hypothesis that if and conditional and were variants in complementary distribution.